The freedom of movement of persons in the EU and it´s present major obstacles - Chikhradze, Anano (2017)
Nicht vorhanden Freedom of movement is one of the four basic freedoms of the single market – the others being free movement of capital, goods and services. These freedoms were enshrined in 1957 in the Treaty of Rome, which established the EU’s predecessor, the European Economic Community (EEC). Freedom of movement began as a way to encourage people to travel to fill jobs after the Second World War. The idea was that a mobile workforce would help boost the economies of the EU's six founding members, and perhaps discourage future conflict on the continent. Almost 60 years on, the system allows citizens to work, study and retire anywhere in the European Union – plus Norway, Liechtenstein and Iceland, all three of which joined the European Economic Area (EEA) and are governed by the four freedoms. There's also Switzerland, which has a bilateral deal with the EU when it comes to border controls. This final thesis consists of three main parts. The first chapter provides an overview of the theoretical concept of free movement. This part consists of two sections and three subsections, describing a free movement of goods, services and capital. The section one discusses the history of a single market, defines the differences between internal, single and common market, explains the nature of four freedoms of the EU, while section two discusses four freedoms of the EU. Chapter one provides background to the detailed analysis of the free movement of persons. Research also shows that free movement has not had a negative effect on the employment rates and wages of nationals of the host country. Workers from the newer EU countries generally take lower skilled jobs in sectors such as agriculture, care services, catering, cleaning, and construction. In practice, this puts them in competition for jobs with lower skilled workers from outside the EU, rather than nationals. Restricting free movement could lead to a shortage of workers in certain sectors. Free movement rights have not only been used by citizens from newer EU member countries. Research shows that free movement is a two-way street. Also, thesis touches the nowadays problems like Brexit. Free movement of persons continues to be debated in the UK after the Brexit referendum and the EEA Agreement is often referred to regarding the UK's future relationship with the EU. This post intends to address two differences in the right to free movement of persons in a model of association with the EU outside membership – the EEA Agreement compared to the right to free movement of persons in the EU. The EEA Agreement extends the EU internal market to include three of the parties to the European Free Trade Association (EFTA) – Norway, Iceland and Liechtenstein – but without membership in the Union. The extension of the internal market means, in principle, parallel rights and obligations in the area of free movement (including the right to free movement of persons) and competition law. Nevertheless, certain products (fish and agricultural products, see Article 8(3) EEA) and tax harmonisation are outside the scope of the Agreement.